NCSSD-YOLO: a non-causal state space duality-based instance segmentation model for pacific white shrimp - Weiqiang Ni; Chenqing Zhang; Yiqing Zhang; Siyi Li; Haitao Wang; Chenchen Wu; Lin Luo; Qinglang Liang; Zequn Peng; Shenghua Li; Yanqing Chen; Shiyin Chen; et al. (Aquaculture International, 2026)

VFLING: Vertical Federated Learning for Multi-Omics Data Integration with Graphs - Xiaoli Li; Qi Li; Dedao Lu; Yue Lin; Saba Aslam; Huijun Li; Zequn Zhang; Yuxi Chen; Ruey-Song Huang; Hongyan Wu (Interdisciplinary Sciences: Computational Life Sciences, 2026)

A cascade-responsive fibrous platform combining nanozyme and NO donor therapy for infected diabetic wound healing - Zequn Lin; Fangrong Tan; Zhanglu Lei; Yangtian Bian; Hongtao Qi; Weichang Li; Qianqian Yu (Chemical Engineering Journal, 2026)

Multi-scale evaluation of six fused evapotranspiration products over mainland China: Accuracy, consistency and uncertainty - Dayang Wang; Dagang Wang; Shaobo Liu; Zequn Lin; Ya Huang; Xiaohang Ma; Mengjiao Wu; Yanyu Ma; Jialu Zhu; B. Larry Li (Journal of Hydrology, 2026)

A knowledge-guided LSTM reservoir outflow model and its application to streamflow simulation in reservoir-regulated basins - Runting Chen; Dagang Wang; Yiwen Mei; Yongen Lin; Zequn Lin; Zhi Zhang; Shengjie Zhuang; Jinxin Zhu; Jonghun Kam; Yiping Wu; Guoping Tang (Journal of Hydrology, 2025)

Systems coupling and cross-diffusion drives complex nested pattern self-organization in predator-prey systems - Tousheng Huang; Yifan Yang; Zhenyu Ren; Ruyin Li; Zequn Lin; Wang Tian (Ecological Complexity, 2025)

Indoor-outdoor interactive thermal response in public building:onsite data collection and classification through cluster algorithm - Zhineng Jin; Yin zhang; Hongli Sun; Meng Han; Yanhong Zheng; Ying Zhao; Wenyang Han; Menglong Zhang; Bin Xu; Zequn Zhang; Borong Lin (Energy and Buildings, 2025)

Spatiotemporal Characteristics of Precipitation Concentration and Their Linkage to Temperature Over China - Zequn Lin; Dagang Wang; Yi Du; Yue Meng (International Journal of Climatology, 2025)
Precipitation concentration represents the temporal unevenness of precipitation over a given period. A higher concentration increases the likelihood of concurrent flooding and drought. While previous studies have primarily focused on precipitation concentration at the daily scale, research on sub‐daily scales remains limited. Furthermore, the impact of temperature on precipitation concentration across various temporal scales is not well understood. In this study, we utilise high‐resolution precipitation products and the Gini index (GI) to examine the spatiotemporal characteristics of precipitation concentration across four different time scales (3, 6, 12‐h and 1‐day) over China. The climatological analysis reveals a gradual increase in precipitation concentration from southeast to northwest China. At shorter temporal scales (3 and 6‐h), Southeastern China exhibits a notable increase in precipitation concentration, while longer scales (12‐h and 1‐day) show a significant decrease throughout most regions of Northwest China. These observed spatiotemporal patterns are closely linked to temperature variations. At the 3‐h scale, precipitation concentration at the 3‐h scale increases with temperature at a nation‐averaged rate of 1.06% °C −1 and decreases to 0.30% °C −1 at the 1‐day scale. Higher temperatures intensify precipitation concentration at the 3‐h scale in Southeast China by increasing the frequency of heavy precipitation events. Meanwhile, in Northwest China, the decline in concentration at the daily scale under warmer conditions is attributed to increased annual precipitation amounts driven by higher temperatures. This study is of great significance, as it provides insight into how the temporal distribution of precipitation in China change under future global warming.

Bifunctional reduced graphene oxide/polyelectrolyte/NiFe layered double hydroxide composites for efficient catalyzed dephosphorylation and 4-nitrophenol reduction - Zijun Xie; Bo Sun; Hongying Lin; Meng Fu; Yi Zhang; Zequn Ma; Xiangming Li (Journal of Water Process Engineering, 2023)

A prognostic cuproptosis-related lncRNA predictive signature for bladder cancer patients - Shaoqin Jiang; Jili Zhang; Qi Fan; Zhihao Li; Ruiling Dou; Zequn Lin; Zhenlin Chen; Yue Xu; Zhangcheng Huang; Jingyuan Lan; Wenwen Lin; Sijie Xu; et al. (Human Cell, 2023)

S100A14 inhibits cell growth and epithelial–mesenchymal transition (EMT) in prostate cancer through FAT1-mediated Hippo signaling pathway - Shaoqin Jiang; Yaru Zhu; Zhenlin Chen; Zhangcheng Huang; Bingqiao Liu; Yue Xu; Zhihao Li; Zequn Lin; Mengqiang Li (Human Cell, 2021)

The effect of excess expression of GFP in a novel heart-specific green fluorescence zebrafish regulated by nppa enhancer at early embryonic development - Wen Huang; Yun Deng; Wei Dong; Wuzhou Yuan; Yongqi Wan; Xiaoyan Mo; Yongqing Li; Zequn Wang; Yuequn Wang; Karen Ocorr; Bo Zhang; Shuo Lin; et al. (Molecular Biology Reports, 2011)